Mexico - Technical Note on Industrial Organization and Competition : Pension System in Mexico (Washington, DC : World Bank, 2022)
Mexico, as many other countries in Latin America, has adopted an individual capitalization pension system. The design of these pension reforms confers the administration of pension funds to private companies. Under these schemes competition plays a key role, keeping prices low, a good quality of service, and an efficient investment allocation. However, the extent of competition in the reformed systems has been a common concern for most of the countries where it has been implemented. Moreover, when competition has been intense, like in Chile between 1994 and 1997, marketing expenses were extremely high. This outcome may not be desirable if it does not benefit future pensioners and is an unnecessary increase in costs of providing the service. The performance of competition in this industry is largely related to the demand characteristics, which is by design highly insensitive to prices, rates of return or quality of service, given that this is a compulsory product with government guarantees. Regulations in this market also significantly affect the way in which competition operates. Aiming to a better degree of competition, the private pension system's regulator in Mexico has introduced innovate rules. These regulations have focus in inducing higher demand elasticity to prices and lowering barriers to entry. This has entailed lower prices, lower profits, and the entrance of new firms. The paper is structured as follows: section A gives pension reform in Mexico; section B gives the role of the government; section C deals with the afore industry; section D is commission structure; section E gives potential barriers to entry; section F focuses on changes in regulation that promote price competition; section G gives comments on policy implications and prospects; and section H gives conclusions and policy recommendations.